Pengaruh Likuiditas terhadap Profitabilitas Melalui Efisiensi Operasi Bank Umum Syariah di Indonesia - Mauluddi, Hasbi Assidiki (Universitas Ma'soem, 2021)
This study aimed to find out the direct influence of liquidity variables on profitability and its indirect influence through variable operating efficiency. Liquidity is proxied with FDR, profitability with ROA, while operating efficiency with BOPO. Path analysis methods are used to analyze the direct or indirect influence of the variables studied. The data used is secondary data of Sharia commercial bank statements in OJK Sharia banking statistics from 2016 to 2020. The results showed that directly the level of liquidity has no significant effect on profitability. Whereas indirectly, through operating efficiency, the level of liquidity has a significant effect on profitability.